A Decolonial Agenda for EU Migration and Asylum Law - Corcodel, Veronica (2024)
This article seeks to advance a decolonial research agenda in EU migration and asylum law, arguing that there is significant scope for further development within existing scholarship. It offers some theoretical tools grounded in postcolonial and decolonial literature, contending that a decolonial project for EU migration and asylum law should critically engage with the enduring epistemic foundations of colonial unequal mobilities and treatment. These include the ‘sedentary bias’ and the ‘cheap labour’ bias, as well as the ways in which these have been shaped by race, gender, class, and other epistemic formations. Building on these insights, the article outlines potential avenues for further research, especially in relation to the EU Schengen regime, the externalisation of EU borders, the construction of the ‘economic migrant’ and the Common European Asylum system.